PENGEMBANGAN EDUKASI PERMAINAN TRADISIONAL MENGGUNAKAN TEKNOLOGI RAMAH ANAK BERBASIS AR UNTUK ANAK SD - Astutik, Rini Puji; Bakhtiar, Afakhrul Masub; Hapsari, Ifahda Pratam; Lesmana, Julmy; Fathoni, Mohammad (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2023)
There are a lot of elementary school students who less know about traditional games such as their parent played when they were child. This case happened due to gadget addiction with many modern variation games which sometimes less educated. This reason why traditional games need to be developed integrated with child-friendly technology that even though it used gadget, however the children are directed to know and learn traditional game and in the next step, they have to play that game. One of child-friendly technology is AR (Augmented Reality) technology that is android application so that the children still feel playing game as usual. This educated development based DGBL (Digital Game Based Learning) which focusing on analysis, design, making, quality checking, implementation and evaluation. To test the system whether it run properly then the expert is needed for verification and validation system and also exploration the implemented result of observation. The result shows the character formation on the children and some benefits. This is good to build the nation in the future which starting from Elementary school students following millennials era and kept traditional games as the nation’s culture wealth.